Exchange rate policy and modelling in India - Dua, Pami; Ranjan, Rajiv (New Delhi, 2012)
Exchange rate fluctuations affect the value of international investment portfolios, competitiveness of exports and imports, value of international reserves, currency value of debt payments, and the cost to tourists in terms of the value of their currency. Movements in exchange rates, therefore, have significant implications for the economy's business cycle, trade, and capital flows. This book provides a comprehensive analysis of the foreign exchange market in India in terms of participants, instruments and the trading platform, as also turnover and forward premia. The book covers four broad areas: (i) various facets of economic policy with respect to the exchange rate; (ii) the recent global financial crisis and the role of exchange rates therein; (iii) the pattern of capital flows and capital account liberalization; and (iv) modelling and forecasting the exchange rate.
Keywords: Economics